2012
DOI: 10.1007/s00216-012-5934-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of sugar analysis and stable isotope ratio mass spectrometry to detect the use of artificial sugars in royal jelly production

Abstract: The effects of feeding bees artificial sugars and/or proteins on the sugar compositions and (13)C isotopic measurements of royal jellies (RJs) were evaluated. The sugars fed to the bees were two C4 sugars (cane sugar and maize hydrolysate), two C3 sugars (sugar beet, cereal starch hydrolysate), and honey. The proteins fed to them were pollen, soybean, and yeast powder proteins. To evaluate the influence of the sugar and/or protein feeding over time, samples were collected during six consecutive harvests. (13)C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 21 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Fructose and glucose together account for 90% of all sugars [ 99 , 104 ]. Sucrose is always present but often in variable concentrations (2.86% according to Kanelis et al [ 99 ], 2.1% according to Kolayli et al [ 23 ], 0.5–2% according to Oršolić [ 105 ], and 0.2% according to Wytrychowski [ 106 ]). Studies have also revealed the presence of other oligosaccharides, such as trehalose, maltose, gentiobiose, isomaltose, raffinose, erlose, and melezitose [ 103 , 104 ].…”
Section: Royal Jellymentioning
confidence: 99%
“…Fructose and glucose together account for 90% of all sugars [ 99 , 104 ]. Sucrose is always present but often in variable concentrations (2.86% according to Kanelis et al [ 99 ], 2.1% according to Kolayli et al [ 23 ], 0.5–2% according to Oršolić [ 105 ], and 0.2% according to Wytrychowski [ 106 ]). Studies have also revealed the presence of other oligosaccharides, such as trehalose, maltose, gentiobiose, isomaltose, raffinose, erlose, and melezitose [ 103 , 104 ].…”
Section: Royal Jellymentioning
confidence: 99%
“…Not only the storage conditions but also the beekeeping practices are mentioned to affect RJ's carbohydrate composition [18]. Yet, the scientific findings do not clarify whether feeding affects the chemical synthesis of the product because some authors claim that it causes changes [19] [20] [21] and some others that it does not [22] [23]. Beekeepers believe that the feeding of bees during RJ production, stimulate workers to increase the quantity of RJ [20] [21] but this notion has not been scientifically proved [21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous applications of IR‐NMR for saccharides were mainly devoted to detection of the addition of exogenous sugars from C 4 and C 3 plants in food products such as honey, royal jelly or maple syrup . An IR‐ 13 C NMR analytical method is available to differentiate between sugars from C 4 metabolism plants (cane, maize) and some crassulacean acid metabolism plants (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A similar limit of about 15% was found for the adulteration of pineapple juice with cane and maize sugar by IR-13 C NMR. 26 The method is therefore not able to detect slight unintended contamination during the sugar production process, but is sufficient to reveal deliberate adulteration.…”
Section: Profiling For Sugar Blendsmentioning
confidence: 99%